Good governance initiatives and reforms - Kothari, Sanjay (New Delhi, 2006)
This book is about Governance Initiatives carried out by way of economic and social reform, and rightsizing measures introduced in the state of Haryana, especially in those areas where the public is affected.
Keywords: Good governance